From E‐VITA open plus to E‐VITA NEO and E‐NOVIA. Issue 5 (19th September 2020) - Jakob, Heinz; Idhrees, Mohammed; Bashir, Mohamad
Abstract: The first clinical implantation of the "Essen I prosthesis" took place in 2005, which was then followed by E‐Vita open plus. With further advancements E‐Vita Neo and E‐Novia was introduced. These devices enable the surgeons to perform frozen elephant trunk in zone 0/1 which eventually reduce the incidence of paraplegia, recurrent laryngeal nerve palsy and proximalization of supraaortic arch vessels. E‐vita open plus and successors alleviate frozen elephant trunk operations rendering more stable results in promoting positive remodelling of the distal aorta.